Revealing polytypism in 2D boron nitride with UV photoluminescence - Jakub Iwański; Krzysztof P. Korona; Mateusz Tokarczyk; Grzegorz Kowalski; Aleksandra K. Dąbrowska; Piotr Tatarczak; Izabela Rogala; Marta Bilska; Maciej Wójcik; Sławomir Kret; Anna Reszka; Bogdan J. Kowalski; et al. (npj 2D Materials and Applications)
Abstract Boron nitride exhibits various crystal structures. The subgroup of layered boron nitrides includes several polytypes such as hexagonal (hBN), Bernal (bBN), and rhombohedral (rBN) BN. The latter two are non-centrosymmetric, potentially leading to piezoelectric or ferroelectric properties. A key challenge related to the polytypism of sp 2-bonded BN is distinguishing between these polytypes. We demonstrate that the optical response of the 4.1-eV defect can be used to differentiate hBN from rBN. Photoluminescence and cathodoluminescence measurements on samples grown by metalorganic vapor phase epitaxy (MOVPE) show a zero-phonon line at 4.096 eV for hBN and 4.143 eV for rBN. Our calculations confirm that the photoluminescence originates from a carbon dimer, CBCN (C2), which is sensitive to the local environments of different polytypes. We demonstrate that different polytypic compositions of hBN and rBN can be achieved by MOVPE, which could pave the way for future applications in large-area van der Waals heterostructures.